ANALYZING STUDENTS’ PERCEPTION TOWARD PAMALI AS SUNDANESSE SOCIAL NORM - Subhan, Ahmad; Ahmad, Egi (IKIP Siliwangi, 2018)
In everyday life we can’t be separated from rules or norms, which is a common practice that benchmarks behavior within a particular group of societies and territorial boundaries. The Sudanese are very understanding and understand the meaning of Pamali as the norm of life or the rules in their culture. The purpose of this research is to know the understanding of Pamali among adolescents who are considered as social norms of Sudanese society. This research consists of 90 respondents by using qualitative method and the data is taken through the result of questionnaire as instrument. Based on data of the researchconcludes that some teenagers know the meaning of Pamali as a social norm applied by their ancestors. but on the other hand they do not believe in Pamali even they are not afraid when they violated Keywords: Pamali, culture , social norm